Niños, niñas y adolescentes con índice de vulnerabilidad y su incidencia en el desarrollo psicosocial de casas familia san Marcelino Champagnat, del cantón Quevedo, provincia de los ríos, año 2015 - Sánchez Peña, Victoria Narcisa (2015)
This research aims to demonstrate the effect generated by risk factors in the physical, cognitive and emotional development of children and adolescents. This research is focused on the vulnerability of children when they are victims of domestic violence, sexual abuse, physical, psychological and verbal type. Children living in a family environment who witness alcoholism, drug dependency and lack of basic needs due to extreme poverty. It is important that people have the knowledge of the imminent danger of exposing minors to events of violence, problems will directly affect the mental health of a child. Not to seek help with these problems, sadly these behaviors will be repeated in the future